Transition to a product line infrastructure: experience at Akari Software. Issue 9 (2nd September 2014) - Hegarty, Paraic; O'Leary, Eoghan; Dineen, Danny; Bustard, David; Moore, Adrian; Biró, M.; Messnarz, R.; Colomo‐Palacios, R.
ABSTRACT Akari Software offers a family of software products supporting curriculum management in higher education. The work started with one specific commission, but within 4 years, a small product suite had been developed, with ten organisations using customised variants of those products. In effect, a product family had been created but without the underlying structure and processes needed to ensure the efficient creation and maintenance of variants. This is a common issue faced by software companies as their product range expands. In 2010, Akari began making internal changes to develop a product range infrastructure that was suitable both for its existing products and its plans for future growth. The purpose of this paper is to describe the product line transition that occurred, both to share the experience involved and to identify a number of general lessons learned. The work was supported by a FUSION project, funded by InterTradeIreland, undertaken in collaboration with the University of Ulster. Copyright © 2014 John Wiley & Sons, Ltd.